Velveteen rabbit (The) : or how toys become real - Williams, Margery (New York : Little Simon, 1983)
By the time the velveteen rabbit is dirty, worm out, and about to be burned, he had almost given up hope of ever finding the magic called Real.
Keywords: Toys -- Fiction; Children stories